Binary conductive network for construction of Si/Ag nanowires/rGO integrated composite film by vacuum-filtration method and their application for lithium ion batteries. (20th October 2015) - Tang, H.; Xia, X.H.; Zhang, Y.J.; Tong, Y.Y.; Wang, X.L.; Gu, C.D.; Tu, J.P.
Abstract: Construction of high-capacity anode is highly important for the development of next-generation high-performance lithium ion batteries (LIBs). Herein we fabricate Si/Ag nanowires/reduced graphene oxide (Si/Ag NWs/rGO) integrated composite film by introducing binary conductive networks (Ag NWs and rGO) into Si active materials with the help of a facile vacuum-filtration method. Active Si nanoparticles are homogeneously encapsulated by binary Ag NWs-rGO conductive network, in which Ag NWs are interwoven among the rGO sheets. The electrochemical properties of the integrated Si/Ag NWs/rGO composite film are thoroughly characterized as anode of LIBs. Compared to the Si/rGO composite film, the integrated Si/Ag NWs/rGO composite film exhibits enhanced electrochemical performances with higher capacity, better high-rate capability and cycling stability (1269 mAh g −1 at 50 mA g −1 up to 50 cycles). The binary conductive network plays a positive role in the enhancement of performance due to its faster ion/electron transfer, and better anti-structure degradation caused by volume expansion during the cycling process.